Digitale Spiele: interdisziplinäre Perspektiven zu Diskursfeldern, Inszenierung und Musik - Hust, Christoph; Borchert, Ineke (Edition Kulturwissenschaft, 2018)
Tetris, World of Warcraft, Pokémon Go & Co. - computer and consol games illuminated from perspectives based on cultural studies.